ONA TILI DARSLARIDA O‘QUVCHILARNI TIL HODISALARINI KUZATISHGA O‘RGATISH - Bekchanova Muqaddam; Sadullayev Shohruh (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2021)
This paper makes analyses of the learning process of the mother language. In this case, language points were discussed by various people and researchers. Outcomes and shortcomings were pinpointed in conclusions points as a whole.